Incidence of COVID-19 in random trauma patients at DHQ Teaching Hospital, Rawalpindi, measures to prevent its spread among patients and health care workers - Tariq Nawaz ,Bilal Mehmood ,Muhammad Waqas Ayub ,Irfan Malik ,Umar Qaisar (Journal of Rawalpindi Medical College, 2020)
Background: The objective of the study was to see the incidence of COVID-19 positive, in random trauma patients received in the emergency of abdomen or chest may be penetrating or blunt. Materials and Methods: This study was conducted in the Accident and Emergency department of District Head Quarter Hospital, Rawalpindi. All trauma patients of abdomen or chest either penetrating or blunt admitted from 1-3-20 to 10-6-20 were included, irrespective of age, gender, comorbidities, and COVID-19 status at the time of admission to hospital. Also to see steps of preventive measures taken in the emergency department, operation theatres, and inwards. Results: Total number of trauma patients received in the emergency department of District Headquarter Hospital Rawalpindi during this period was 163. Total male patients: 116. Total female patients:47. Penetrating injuries (firearm or stab wounds): 93. Blunt injuries: 70. All the penetrating injuries were operated as an emergency. Among blunt injuries, 51 were operated 19 were treated conservatively. Preoperatively none of the patients’ COVID-19 test was performed because none of them showed any symptoms likely of COVID-19 such as chest infection, flue, malaise, or fever. After the second postoperative day, 12 of the patients developed respiratory distress and their COVID-19 test was sent. Out of 12 patients, 7 turned out to be COVID-19 positive. Other on the second or third postoperative day 7 patients had fever without chest symptoms and underwent COVID-19 testing. 3 turned out to be COVID-19 positive. So a total of 11 patients were found to be positive for COVID-19. The percentage became 6.7% which is quite high. Conclusion: From this study, its clear in acute trauma patients where you can’t go for the COVID-19 test even then we have to operate may be positive. So every trauma patient should have suspected COVID-19 positive and preventive measures should be taken starting from the emergency department till operation theatres.